Avaliação físico-química e microbiológica de águas residuárias da UEG-Câmpus Anápolis submetidas a diferentes sistemas de tratamento - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The use of natural systems such as biological filters and wetlands built into wastewater treatment has become increasingly important because of the ability of these systems to promote organic matter degradation and to remove large amounts of nutrients, heavy metals and microorganisms. The objective of this study was to characterize the wastewater from the septic tank of UEG-Campus Anápolis through physico-chemical and microbiological parameters of water quality, in order to evaluate the efficiency of two treatment systems: six biological filters each which contain a different substrate, being: Bambusa gracilis, Bambusa multiplex, expanded clay, gravel 0 and gravel 2 and constructed horizontal wetland of subsurface flow. In the filter systems, the substrate that showed the greatest efficiency in the removal of organic matter was the Bambusa multiplex with 84.40% and the substrate was the expanded clay with 48.0%. In the constructed wetland system, the percent efficiency results found for nutrient removal ranged from 57.90 to 94.70%, heavy metals from 50.0 to 100.0% and organic matter from 87.0 to 91.0%. In general, it was found that the operating time of the biological filter system was insufficient to draw precise conclusions as to the efficiency of the parameters analyzed in the system. It is also concluded that the built wetland system can be used in the treatment of wastewater from septic tanks at both secondary and tertiary level due to its high percentage efficiency in the removal of nutrients, organic matter and heavy metals. In the general evaluation of the results obtained, the systems studied prove to be a versatile, sustainable and economical treatment option, being able to be used as a complementary system to the treatment by septic tank used in UEG-Campus Anápolis.
Keywords: Águas residuárias; Tratamento de efluentes; Wetlands construídos; Filtros biológicos; Wastewater; Effluent treatment; Wetlands built; Biological filters; CIENCIAS EXATAS E DA TERRA::QUIMICA